Perceptions, attitudes and practices of menstrual hygiene among rural and urban high school girls in a northern district of Kerala - S. V., Aswathy Raj; C., Prabhakumari (International Journal Of Community Medicine And Public Health, 2020)
Background: Menstrual hygiene practices are poor in developing countries and exist as an insufficiently acknowledged problem. The objective of this study was to assess and compare perceptions, attitudes, and practices among rural and urban high school girls. Methods: Cross sectional study was conducted in randomly selected 4 rural and 4 urban schools in Kozhikode district by cluster sampling method. 8th and 9th standard school girls who attained menarche were included in study. Data were collected by questionnaire. Results: Most of the girls gained information prior to menarche. Girls who wrongly perceived cause of menstruation was more in rural subjects compared to urban. Almost half of girls were either unaware or wrongly perceived source of bleeding. 50.9% urban girls were not mentally prepared for menarche as compared to 44.4% of rural girls. Majority of rural girls shared information with mothers compared to urban. 83.9% in rural and 78.2% urban had an attitude of menstruation as an unclean phenomenon. Majority had some form of restrictions during menstruation. Higher proportion of urban girls used sanitary pad compared to rural. 50.3% of urban and 42.8% of rural girls were disposing absorbent in to closet when at school. Among pad users, similar findings were noted at home also. A higher proportion of urban girls (55.9%) practiced good menstrual hygiene as compared to average hygiene practiced by rural girls (48.9%). Conclusions: The study shows significant rural-urban differences in perceptions, attitudes, and practices on menstrual hygiene in both areas.